1989
DOI: 10.1128/iai.57.8.2390-2396.1989
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Fc receptor and respiratory burst in killing of Rickettsia prowazekii by macrophagelike cell lines

Abstract: It is known that the virulent strain of Rickettsia prowazekii grows in macrophagelike cell lines, but if the rickettsiae are treated with antirickettsial serum before infection, the intracellular rickettsiae fail to grow and are destroyed. The uptake of rickettsiae by macrophagelike cell lines was increased by treatment of the rickettsiae with immune serum and with purified immunoglobulin G (IgG) from this serum but not by treatment with the F(ab')2 fragment derived from this IgG. This suggested that the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Neither the Breinl strain nor the Madrid E strain of R. prowazekii induces a respiratory burst in RAW264.7 cells (14,21); hence, differential induction or sensitivity to the products of the respiratory burst is not an adequate explanation. Winkler and Daugherty (34) provided evidence that in RAW264.7 cells, the poor growth of the Madrid E strain relative to the Breinl strain is a function of the cytoplasm of the macrophagelike cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neither the Breinl strain nor the Madrid E strain of R. prowazekii induces a respiratory burst in RAW264.7 cells (14,21); hence, differential induction or sensitivity to the products of the respiratory burst is not an adequate explanation. Winkler and Daugherty (34) provided evidence that in RAW264.7 cells, the poor growth of the Madrid E strain relative to the Breinl strain is a function of the cytoplasm of the macrophagelike cells.…”
Section: Discussionmentioning
confidence: 98%
“…Later work indicated that the Madrid E strain also grows poorly in several mouse macrophagelike cell lines that support good growth of the virulent Breinl strain (22). The ability of R. prowazekii Breinl to grow in human monocyte-derived macrophages or mouse macrophagelike cells is inhibited by pretreatment of the rickettsiae with antirickettsial serum, immunoglobulin G (IgG), or F(ab')2 fragments derived from IgG (3,14,22).…”
mentioning
confidence: 99%
“…Τα αντισώματα παίζουν ρόλο στην είσοδο των ρικετσιών στα μακροφάγα. Επεξεργασμένες με ανοσοορό ρικέτσιες μπαίνουν στα μακροφάγα, αφού πρώτα συνδεθούν με τους Fe υποδοχείς (Keysary et al, 1989). Αδιευκρίνιστη παραμένει η συμβολή των αντισωμάτων στην εξάλειψη, τόσο των ενδοκυττάριων όσο και των εξωκυττάριων ρικετσιών (Keysary et al, 1989& Williams et ai., 1986.…”
Section: ανοσολογιαunclassified
“…Τα αντισώματα παίζουν ρόλο στην είσοδο των ρικετσιών στα μακροφάγα. Ο Keysary et al έδειξαν ότι επεξεργασμένες με ανοσοορό ρικέτσιες μπαίνουν στα μακροφάγα, αφού προηγούμενα συνδεθούν με τους Fe υποδοχείς (Keysary et al, 1989). Η συμβολή όμως των αντισωμάτων στην εξάλειψη, τόσο των ενδοκυττάριων όσο και των εξωκυττάριων ρικετσιών δεν έχει διασαφηνισθεί (Keysary et al, 1989;Williams et al, 1986).…”
Section: χυμική ανοσίαunclassified